Utilizing Inverse Kinematics for Precise Guidance in Planning 6-DoF Robot End-Effector Movements - Heru Suwoyo; Andi Adriansyah; Julpri Andika; Muhammad Hafizd Ibnu Hajar; Rizky Dinata; Thathit Gumilar Triwidya Mochtar; Muhammad Yusuf; Fajri Rezki Hutomo (International Journal of Engineering Continuity, 2024)
The solution of the kinematic inverse determines a substantial part of the robotic arm's control accuracy. Researchers frequently employ standard problem-solving techniques such as numerical, algebraic, iterative, and geometric methods. Although geometric like trigonometrical method has been widely studied, and their application is strongly dependent on the shape and dimensions of the robot. The complexity of the steps makes this approach difficult for researchers. In order to give a clearance and easiness, the step-by-step features of inverse kinematics are described in this research. The study begins with forward kinematics and refers to the DH-parameter in Homogeneous Matrix Transformations calculation. The existence of specific elements applied to mathematical derivation constituted the basis of forward kinematic discussions. And based on geometrical analysis, the inverse kinematic is then derived. Furthermore, simulations are performed to demonstrate the actual implementation of IK and the solution is then used to initiate the path planning process.